Kinetic analysis of endosome processing : maturation of early endosomes and vesicular traffic to lysosomes - Stroud, Evelyn Joy (Division of Medical Biochemistry and Structural Biology, 2018)
The present study was undertaken to establish the mechanism(s) involved in the endocytic pathway, in particular, early endosome processing and delivery to the lysosomes. Two models for endosome processing have previously been proposed in the literature, namely the maturation and vesicular traffic models. The general consensus has been an early phase of intermingling of the endocytic contents markers within early endosomes that mature to form non-fusogenic late endosomes (maturation model). This maturation phase is followed by a segregation phase where intermingling of contents between vesicles no longer takes place. To establish the mechanism(s) involved in early endosome processing and delivery to lysosomes, a kinetic analysis was made using results from cellular fluid-phase uptake assays. This unique approach offers an alternative view to previous studies on the mechanisms in operation during endocytic processing. The results and conclusions made could thus confirm or disprove previously proposed mechanisms.